2000
DOI: 10.1046/j.1468-2982.2000.00129.x
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Term Effects of Homeopathic Treatment of Chronic Headaches: 1 Year Follow Up

Abstract: Little is known about the long-term effects of homeopathic treatment. Following a double-blind, placebo-controlled trial of classical homeopathy in chronic headaches, we conducted a complete follow-up study of all trial participants. All patients enrolled in the double-blind study were sent a 6-week headache diary, a follow-up questionnaire. Eighty-seven of the original 98 patients enrolled returned questionnaires, 81 returned diaries. There was no additional change from the end of the trial to the 1-year foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
5

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 4 publications
1
8
0
5
Order By: Relevance
“…Physio the ra pie al lein ist nicht wirk sam, verbes sert aber in Kom bi na ti on die Rate der Be trof fe nen, die auf ver hal tens the ra peuti sche Ver fah ren an spre chen. Für die Homöo pa thie lie gen bei Er wach se nen ran domi sier te, pla ce bo kon trol lier te Stu di en vor, die kei ne Wirk sam keit be le gen [10,27,28,29]. Aku punk tur re du ziert die Häu fig keit von Mi grä ne at ta cken.…”
Section: Nicht Me DI Ka Men Tö Se the Ra Pie For Men Bei Der Mig Rä Neunclassified
“…Physio the ra pie al lein ist nicht wirk sam, verbes sert aber in Kom bi na ti on die Rate der Be trof fe nen, die auf ver hal tens the ra peuti sche Ver fah ren an spre chen. Für die Homöo pa thie lie gen bei Er wach se nen ran domi sier te, pla ce bo kon trol lier te Stu di en vor, die kei ne Wirk sam keit be le gen [10,27,28,29]. Aku punk tur re du ziert die Häu fig keit von Mi grä ne at ta cken.…”
Section: Nicht Me DI Ka Men Tö Se the Ra Pie For Men Bei Der Mig Rä Neunclassified
“…Many good quality studies of the last 12 years have yielded negative results, for instance, concerning systematic reviews and meta-analyses [3][4][5][6][7][8][9][10][11] ; infections of the upper respiratory tract and allergic rhinitis 12,13 ; post-operative ileus 14 ; asthma 15 ; warts [16][17][18] ; pain relief and muscle soreness [19][20][21][22][23] ; treatment of adenoid vegetation 24 ; chronic headache [25][26][27][28] ; ear inflammation 29,30 ; eczema 31 ; arthritis 32,33 ; bruising 34,35 ; anxiety 36 ; "provings" (see below) with belladonna, arnica, Pulsatilla and mercury [37][38][39][40][41] and "aggravations" ("good" worsening of symptoms, said by homeopaths to precede patient recovery) 42 . Detailed comments on many of these studies are published 2,5,43 .…”
Section: Clinical Trialsmentioning
confidence: 99%
“…17 18 In addition, a follow up study relating to a trial of classical homoeopathy included in a review on homoeopathic prophylaxis of headaches and migraine was identified 21 and will be described later. 22 In the earliest trial patients with mild traumatic brain injury were recruited. 17 After 4 months, statistically significant effects in favour of homoeopathy were observed for changes in some scores of physical, cognitive, and affective symptoms and functional disability.…”
Section: Reviews Of Individualised (Classical) Homoeopathymentioning
confidence: 99%
“…37 At 1 year, between group differences for headache frequency, duration, and intensity were still not statistically significant. 22 Asthma A well conducted review assessed the effectiveness of homoeopathy in treating stable chronic asthma or asthma-like symptoms. 26 The three included RCTs were of variable methodological quality.…”
Section: Delayed Onset Muscle Soreness (Doms)mentioning
confidence: 99%